Efficacy of anthelminthic drugs and drug combinations against soil-transmitted helminths: a systematic review and network meta-analysis. - Clarke, N.; Doi, S.; Wangdi, K.; Chen, Y.; Clements, Archie; Nery, S. (Oxford University Press, 2018)
Background: Periodic mass distribution of benzimidazole anthelminthic drugs is the key strategy to control soil-transmitted helminths (STH) globally. However, benzimidazoles have low efficacy against Trichuris trichiura, and there are concerns about benzimidazole resistance potentially emerging in humans. Therefore, identifying alternative drug regimens is a pressing priority. We present a systematic review and network meta-analysis, comparing the efficacy of 21 different anthelminthic drug regimens, including standard, novel, and combination treatments. Methods: We searched PubMed, MEDLINE, Embase, Web of Science, and Cochrane databases and identified studies comparing anthelminthic treatments to each other or placebo. The outcomes calculated were relative risk (RR) of cure and difference in egg reduction rates (dERR). We used an automated generalized pair-wise modelling framework to generate mixed treatment effects against a common comparator, the current standard treatment (single-dose albendazole). This study is registered with PROSPERO (CRD42016050739). Findings: Our search identified 4876 studies, of which 114 were included in meta-analysis. Results identified several drug combinations with higher efficacy than single-dose albendazole for T. trichiura, including albendazole-ivermectin (RR of cure 3.22, 95%CI 1.84-5.63; dERR 0.97, 95%CI 0.21-1.74), albendazole-oxantel pamoate (RR 5.07, 95%CI 1.65-15.59; dERR 0.51, 95%CI 0.450-0.52), mebendazole-ivermectin (RR 3.37, 95%CI 2.20-5.16), and tribendimidine-oxantel pamoate (RR 4.06, 95%CI 1.30-12.64). Interpretation: There are several promising drug combinations that may enhance the impact of STH control programs on T. trichiura, without compromising efficacy against A. lumbricoides and hookworm. We suggest further, large-scale trials of these drug combinations and consideration of their use in STH control programs where T. trichiura is present.